SAT0021 Type 2 Innate Lymphoid Cells Are Rapidly and Persistently Recruited in Experimental Fibrosis and Their Counts Correlate with The Severity of Skin and Lung Fibrosis in Systemic Sclerosis. (15th July 2016) - Wohlfahrt, T.; Weber, S.; Englbrecht, M.; Dees, C.; Beyer, C.; Distler, O.; Schett, G.; Distler, J.; Ramming, A.
Abstract : Background: Type 2 innate lymphoid cells (ILC2s), are recently identified as population of cells with lymphoid morphology lacking re-arranged antigen-specific receptors. Objectives: We aimed to evaluate the contributive role of ILC2s in the pathogenesis of systemic sclerosis (SSc), in particular their levels and correlations with fibrotic manifestations in SSc and various fibrotic mouse models. Methods: Human blood samples and skin sections (69 patients with SSc and 47 healthy controls) as well as skin and lung tissue of various fibrotic mouse models were analyzed by flow cytometry and immunohistochemistry using two complementary panels of markers each. ILC2s were further phenotyped for activation and homing parameters. ILC2 counts were correlated with clinical manifestations of SSc Results: Significantly elevated numbers of ILC2s were detected in the skin (10-fold increase) and blood (4-fold increase) of SSc patients by two independent established sets of ILC2 markers compared to healthy controls. In contrast to circulating ILC2s, skin-resident ILC2s express various activation markers and stained positive for skin homing markers. Furthermore, our data suggest that ILC2s might be involved in the pathogenesis of fibrosis in SSc by showing multiple associations of ILC2 counts with fibrotic manifestations in SSc patients. Significantly higher frequencies were observed in diffuse cutaneous (dc)SSc patients compared to limited cutaneous SSc (lcSSc). The modified Rodnan Skin Score (mRSS) positively correlated with ILC2 counts and pulmonary involvement. In parallel, we detected significantly elevated numbers of ILC2s in the fibrotic skin of bleomycin-induced and DNA topoisomerase I-induced mice compared to control mice. Moreover, in the tight-skin (Tsk)-1model of fibrosis resembling less inflammatory stages of SSc significantly increased ILC2 counts were detected compared to control mice. Kinetic analyses revealed an early upregulation of ILC2s in experimental models of fibrosis. In contrast to lineage positive lymphocytes that peak at early inflammatory stages of fibrosis, however disappear over time, ILC2s persist also in later stages of established fibrosis. Conclusions: Here, we provide first evidence for a role of ILC2s in the pathogenesis of SSc by demonstrating increased ILC2 counts in the skin and blood of human SSc patients. These findings were indirect supported by elevated numbers of ILC2s in the fibrotic skin and lung sections of various mouse models for SSc, reflecting different pathophysiological aspects of the disease. Proliferation of ILC2s in the fibrotic skin, the activated state of dermal ILC2s and correlations of ILC2 counts with dermal and pulmonary fibrosis together with supporting findings of these cells in fibrotic areas of murine skin and lung samples suggest a central role of ILC2s in the pathogenesis of fibrosis. Disclosure of Interest: None declared